Investigate the Relationship between the Vehicle Roll Angle and Other Factors When Steering. (28th January 2023) - Nguyen, Duc Ngoc; Nguyen, Tuan Anh
Abstract : Rollover is a dangerous phenomenon. It is closely related to the vehicle roll angle. The greater the roll angle, the greater the risk of rollover. The vehicle roll angle when steering depends on many factors, such as the size of the vehicle, speed of movement, steering angle, etc. In this paper, the author has simulated the oscillation of a car when steering using MATLAB® software with three specific cases. The purpose of the study is to evaluate the dependence of the roll angle on other factors. Each case handles two scenarios: vehicle speed change (fixed height) and vehicle height change (fixed speed). The model of a complex dynamic, a combination of many nonlinear components, is used to simulate vehicle oscillations. According to the study's results, the roll angle will increase if the speed or the distance from the center of gravity (CG) to roll axis (RA) increases, respectively. Once the roll angle's value rises, the roll index also increases, which causes the dynamic force at the wheel to decrease. If the vertical force at the wheel approaches zero, a rollover may occur. The rollover phenomenon occurred in the second case, corresponding to speeds v = 80 (km/h) and v = 85 (km/h). The peak values of the roll angle are 7.77° and 7.63°, respectively. This result helps to identify the factors affecting the rollover phenomenon more clearly.